Resposta :
Explicação passo-a-passo:
a) (-13)2 + V81 - 3. V625 - (-3)
= (-26) + 9 - 3 × 25 + 3
= -26 + 9 - 75 + 3
= -16 - 75 + 3
= -88
b- - 1. ( -25) + (-3)3
= -1 × (-25) + (-9)
= 25 + (-9)
= 16
Como resolver ?
- Potência e/ou Raiz.
- Multiplicação e/ou Divisão.
- Soma e/ou subtração.
Vamos resolver!!!
a)
(-13) × 2 + √81 - 3 × √625 - (-3)
- -13 × 2 + 9 - 3 × 25 - (-3)
- -26 + 9 - (-75) - (-3)
- 61
b)
-1 × (-25) + (-3) × 3
- 25 + (-9)
- 16
Espero ter ajudado!!!
![Ver imagem АНОНИМ](https://pt-static.z-dn.net/files/d1f/c8211389d3555f3fdbf42efd952aaa81.jpg)